Analysis of the Effectiveness of Cloud-Based Learning Management Systems (LMS) in University - Munawwaroh, Izzatul; Baharun, Hasan (International Journal of Instructional Technology, 2022)
This research evaluates the effectiveness of implementing a cloud-based Learning Management System (LMS) at universities. This research stems from the need to overcome the challenges of accessibility, flexibility and efficiency in an increasingly digital learning process. Using a qualitative approach and case studies, data was collected through in-depth interviews and observations at several university institutions implementing cloud-based LMS. The research results show that this system significantly improves real-time access to learning materials, allows flexibility in the teaching and learning process, and increases administrative efficiency and interaction between lecturers and students. However, this research also faces several limitations and challenges. One of the main challenges is resistance to change among lecturers and students who have yet to become familiar with cloud technology and limited technological infrastructure in some institutions, which hinders optimal implementation. Additionally, although the results show significant benefits, this research is limited to a limited number of institutions. It needs to include a long-term analysis of the impact of cloud-based LMS on educational quality and student satisfaction. These findings show that cloud-based LMS strengthens educational management and creates a more responsive and adaptive learning environment. This research provides a strong justification for the adoption of cloud technology at universities and provides a basis for further research into its long-term impact.